Bioequivalence of a single dose of two palbociclib formulations in healthy Chinese subjects under fasting conditions: a two-period crossover study with rabeprazole pre-treatment - Bai, Wanjun; Shi, Shuo; Yin, Deliang; Guo, Caihui; Song, Haojing; Hu, Yiting; Gao, Jin; Qiu, Bo; Zhang, Xueyuan; Bi, Lusha; Wu, Huizhen; Dong, Zhanjun (Frontiers in Pharmacology, 2025)
ObjectivesThis study assessed the pharmacokinetics, safety, and bioequivalence of generic and original palbociclib tablets in healthy Chinese subjects under fasting conditions with rabeprazole pre-treatment.MethodsThis was a single-dose, randomized, open-label, two-period crossover bioequivalence study conducted under fasting conditions with rabeprazole pre-treatment. In each trial, healthy Chinese subjects received 40 mg oral rabeprazole enteric-coated tablets once daily before breakfast for 6 days. Following an overnight fast of at least 10 h, they took the seventh dose of rabeprazole and maintained fasting. They then received a single 125 mg oral dose of either the test or reference palbociclib tablet, followed by a 14-day washout interval between periods. Blood samples were collected from 0 to 96 h post-dose in each period, and palbociclib plasma concentrations were determined using a validated method. The primary pharmacokinetic parameters were calculated using the non-compartmental method. The geometric mean ratios of the two formulations and the corresponding 90% confidence intervals were acquired for bioequivalence analysis. The safety of both formulations was also evaluated.ResultsThe 90% confidence intervals for the primary pharmacokinetic parameters of Cmax (84.53%–91.72%), AUC0-t (87.81%–92.49%), and AUC0‐∞ (87.59%–92.03%) all fell within the 80.00%–125.00% bioequivalence range. No serious adverse events occurred during the study.ConclusionThe trial confirmed that the pharmacokinetic parameters of the generic and original palbociclib tablets were bioequivalent in healthy Chinese subjects under fasting conditions with rabeprazole pre-treatment. Both formulations were safe and well tolerated.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn, identifier CTR20232617; https://www.chictr.org.cn, identifier ChiCTR2400084355.